"People's Diplomacy": The Diplomatic Front of North Vietnam During the War Against the United States, 1965-1972 - Mehta, Harish C. (My University, 2009)
This doctoral dissertation investigates how the Democratic Republic of Vietnam (DRV, or North Vietnam), under the leadership of President Ho Chi Minh, created a "diplomatic front" to implement "people's diplomacy." The main focus is on the period from 1965-1972 when the DRV needed these strategies to win worldwide support and sympathy for the Vietnamese Revolution. The diplomatic front consisted of Vietnamese writers, cartoonists, workers, women, students, artistic performers, filmmakers, architects, medical doctors and nurses, academics, lawyers, and sportspersons. Research in Vietnamese, American, and Canadian archives reveals that the front forged important links with antiwar activists abroad, thus lending greater credibility to their efforts to portray North Vietnam in a positive light. People's diplomacy made it difficult for the United States to prolong the war because the North Vietnamese, together with the peace movment abroad, brought popular pressure on U.S. President Lyndon Johnson to end the war. People's diplomacy was much more effective than traditional DRV diplomacy in gaining the support and sympathy of Westerners who were averse to communism. People's diplomacy damaged the reputation of the United States by exposing U.S. war crimes and casting North Vietnam as a victim of American imperialism. As a result, many of America's Western allies did not send troops or provide aid to South Vietnam. People's diplomacy also helped North Vietnam gain crucial economic, military, and diplomatic support from the Soviet Union, China, Eastern Europe, Cuba and North Korea.
Keywords: North Vietnam, "diplomatic front", "people's diplomacy", Revolution, United States, economic